Analisis Kinerja Pegawai dalam Pelayanan Administrasi di Kantor Kepala Desa Maliran Kecamatan Ponggok Kabupaten Blitar - Erysma Prihandini; Abdul Aziz Al kaharudin; Sutowo Sutowo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Effective, efficient, and accountable public services are one of the fundamental pillars of good governance. At the village level, the success of these services is highly dependent on the performance of government officials, particularly in administrative services that directly address the community’s basic needs. This study aims to analyze employee performance in administrative services at the Maliran Village Head Office, Ponggok Subdistrict, Blitar Regency, and to identify obstacles faced during the service process. A descriptive qualitative research method was employed, with data collected through observation, interviews, and documentation. The findings indicate that employee performance can be categorized as fairly good based on ten performance indicators: work quality, work quantity, timeliness, effectiveness, independence, reliability, responsiveness, assurance, empathy, and tangible evidence. These aspects reflect that village officials are generally able to carry out their duties in meeting the administrative needs of the community. However, several obstacles remain, including reliance on digital technology that is not supported by adequate infrastructure, particularly the frequent occurrence of power outages which disrupts the continuity of services. The study highlights the importance of strengthening digital infrastructure, enhancing technical training for village officials, and ensuring the availability of backup systems to anticipate service interruptions. These efforts are essential to improve service delivery, strengthen public trust, and support the realization of good governance at the village level.